2007
DOI: 10.1093/ajcn/86.2.388
|View full text |Cite
|
Sign up to set email alerts
|

Iron bioavailability from maize and beans: a comparison of human measurements with Caco-2 cell and algorithm predictions

Abstract: Background: An in vitro digestion and Caco-2 cell model may predict iron bioavailability to humans; however, direct comparisons are lacking. Objective: The objective was to test the differences in iron bioavailability between 2 maize varieties and 2 bean varieties (white beans and colored beans) by comparing human, Caco-2, and algorithm results. Design: Two randomized, 2 ҂ 2 factorial experiments compared women's iron absorption from 2 maize varieties (ACR and TZB; n ҃ 26) and 2 bean varieties (great northern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 48 publications
3
62
2
Order By: Relevance
“…This could indicate that factors which are responsible for a decrease of the phytate content in soybean grain could also increase the Fe content to a high degree (explained variance of 2.185), while β-carotene and Mg were positively related, but to a lesser extent (explained variance of 0.884), and were influenced by other factors. Moreover, studies with maize and beans did not support a lower Fe availability from grains with a slightly higher phytate content (Beiseigel et al, 2007), while significance was given to factors that improve Fe availability, such as ascorbic acid, as well as β-carotene, which was included in the present study. Table 6.…”
Section: Resultscontrasting
confidence: 56%
“…This could indicate that factors which are responsible for a decrease of the phytate content in soybean grain could also increase the Fe content to a high degree (explained variance of 2.185), while β-carotene and Mg were positively related, but to a lesser extent (explained variance of 0.884), and were influenced by other factors. Moreover, studies with maize and beans did not support a lower Fe availability from grains with a slightly higher phytate content (Beiseigel et al, 2007), while significance was given to factors that improve Fe availability, such as ascorbic acid, as well as β-carotene, which was included in the present study. Table 6.…”
Section: Resultscontrasting
confidence: 56%
“…Many studies provide support for the validity of using cell ferritin as an index of bioavailability and this model was qualitatively and quantitatively validated under different conditions (Au & Reddy, 2000;Glahn, Lai, Hsu, Thompson, & Van Campen, 1998;Glahn, Rassier, Goldman, Lee, & Cha, 2000;Glahn, Wien, Van Campen, & Miller, 1996;Glahn, Wortley, South, & Miller, 2002;Hunt & Roughhead, 1999;Roughhead & Hunt, 2000). However, the in vitro digestion/Caco-2 model requires experienced technicians and good quality cell-culture facilities to obtain reproducible results (Argyri, Birba, Miller, Komaitis, & Kapsokefalou, 2009) and according to Beisegel et al (2007) the in vitro digestion/Caco-2 model has limitations in the predictions of iron bioavailability in certain food matrices like beans.…”
Section: Introductionmentioning
confidence: 97%
“…Results from quantitative studies comparing in vivo human to in vitro Caco-2 iron uptake results for semisynthetic meals have shown that human and Caco-2 data generally agree [9][10][11]. Yun et al [10] determined that the Caco-2 model can be used to estimate human iron bioavailability from complex meals if the results can be compared as absorption ratios, which are the iron absorption at a given level of promoter or inhibitor divided by the iron absorption without the promoter or inhibitor present.…”
Section: Introductionmentioning
confidence: 99%